1995
DOI: 10.1063/1.1146504
|View full text |Cite
|
Sign up to set email alerts
|

Novel cathode for field-emission applications

Abstract: A CsI salt-based cathode which is capable of producing a modest perveance, 10 s of A/cm2 electron beam for several microseconds pulse lengths, and has little susceptibility to diode closure has been experimentally characterized. This explosive field-emission C&coated carbon fiber cathode has operated in modest 10T5 Torr vacuums at voltages up to 160 kV, and can easily be configured to provide space-charge-limited solid or annular electron beams in arbitrarily large diameter configurations. The CsI cathode has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…21 In a planar vacuum diode, the electron energy can be many keV and the pressure sufficiently low so that the electron mean free path is greater than the interelectrode distance. 22 Consequentially, the maximum electron energy is equal to the applied potential difference between the electrodes, 21 which is similar to the polywell device. A planar vacuum diode was constructed, as shown in Fig.…”
Section: The Vacuum Diodementioning
confidence: 99%
“…21 In a planar vacuum diode, the electron energy can be many keV and the pressure sufficiently low so that the electron mean free path is greater than the interelectrode distance. 22 Consequentially, the maximum electron energy is equal to the applied potential difference between the electrodes, 21 which is similar to the polywell device. A planar vacuum diode was constructed, as shown in Fig.…”
Section: The Vacuum Diodementioning
confidence: 99%
“…[1][2][3] Nevertheless, the complete physics of the explosive emission process is far from fully characterized. While it has been experimentally observed that anode/cathode materials, anode/cathode temperatures, background vacuums, and cathode coatings (such as cesium iodide) all have dramatic influence on explosive emission operation, 4-8 it is still not possible to quantitatively predict from first principles each effect so that diode design and simulation can progress independent of experimental verification.…”
Section: Motivationmentioning
confidence: 99%
“…Thus, in an effort to increase the total current in the electron beam as opposed to increasing the beam voltage, much research into the cathode emission process has been performed over the past twenty years. [1][2][3] There are a number of specific areas for improvements in cathode technology that will do much to advance the state-of-the-art in HPM generation: emission current density, beam quality, efficiency, fabrication cost, operability in a hostile environment, lifetime, plasma generation, and voltage threshold for emission. The purpose of the Threshold Cathode Test Facility (TCTF) research program is to investigate the electron emission properties of various cathode materials under the HPM-relevant conditions of high electric field stress in a high vacuum environment.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Surface coating with cesium iodide (CsI) on polymer velvet cathode is an alternative and effective strategy to reduce outgassing levels and decrease plasma expansion velocity, due to the low ionization potential and high mass of cesium. 9,18,19 However, the hygroscopicity and oxidizability of CsI in the atmosphere, 20,21 especially in the humid environment, restricted its wide application. Therefore, it is necessary to develop new surface modification technique for polymer velvet cathode to improve the high-current pulsed emission performances.…”
Section: Introductionmentioning
confidence: 99%